Proceedings of the Ocean Drilling Program, 162 Scientific Results 1999
DOI: 10.2973/odp.proc.sr.162.035.1999
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution Pleistocene diatom biostratigraphy of Site 983 and correlations with isotope stratigraphy

Abstract: High accumulation rates and the presence of well-preserved, abundant diatoms in Site 983 sediments from the Gardar Drift gave us the opportunity to refine the Pleistocene diatom biostratigraphic resolution of the high-latitude North Atlantic. Eight Pleistocene diatom datum events are identified and, for the first time, tied directly to the oxygen isotope record and paleomagnetic stratigraphy of Site 983. These datum events are (1) the last occurrence (LO) of Proboscia curvirostris at 0.3 Ma, (2) the LO of Thal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 20 publications
2
36
0
1
Order By: Relevance
“…Site 983 is ideally positioned to register changes in the position of the Arctic Front and thus the extent of the Arctic water mass in the North Atlantic. This has been demonstrated in previous examinations of Site 983 sediments and of its closest neighbor, Site 984, using diatoms and foraminifera respectively [Koç et al, 1999;Wright and Flower, 2002]. The sensitive location of Site 983 may account for the high degree of variability in SSTs and %C 37:4 within glacial/ interglacial stages.…”
Section: Site 983 (North Atlantic)mentioning
confidence: 77%
“…Site 983 is ideally positioned to register changes in the position of the Arctic Front and thus the extent of the Arctic water mass in the North Atlantic. This has been demonstrated in previous examinations of Site 983 sediments and of its closest neighbor, Site 984, using diatoms and foraminifera respectively [Koç et al, 1999;Wright and Flower, 2002]. The sensitive location of Site 983 may account for the high degree of variability in SSTs and %C 37:4 within glacial/ interglacial stages.…”
Section: Site 983 (North Atlantic)mentioning
confidence: 77%
“…These authors concluded based on the absence of production of silica in the surface waters of the GIN seas relative to the region south of Iceland (Koç and Flower, 1998;Koç et al, 1999) that a strong front must have existed near the Greenland-Scotland Ridge during most of the interglacials of the early to mid-Pleistocene (summarized by Raymo et al, 2004). This was reflected by the presence of a pronounced low-δ 13 C water mass at mid-depth throughout the 41 kyr world ∼ 1.8-1.2 Ma.…”
Section: Resultsmentioning
confidence: 99%
“…Koç et al, 1999) is tentatively placed between Samples 303-U1307A-3H-CC and 4H-CC and 303-U1307B-3H-CC and 4H-CC (Fig. F12).…”
Section: Diatomsmentioning
confidence: 99%
“…Peak numbers from 1 to 8 represent the location of the foraminifer ooze layers of Unit I. (Sato et al, 1999) Diatom datum (Koç et al, 1999) Planktonic foraminifer datum (Weaver and Clement, 1987) MIS (Wei, 1993;Sato et al, 1999) Figure F13. Site U1307 downcore relative abundance of calcareous nannofossils, planktonic foraminifers, diatoms, radiolarians, dinocysts, and pollen.…”
Section: Nannofossil (%)mentioning
confidence: 99%
See 1 more Smart Citation